Feasibility Study of Financial Economic on Combination Goat Farming and Cacao Farm By Farmers - S Rusdiana; R. Hutasoit (The International Journal of Tropical Veterinary and Biomedical Research, 2019)
The research was conducted in Sumber Harapan Village, Tinggi Raja District, Asahan Regency, North Sumatra Province, in 2016, using field survey methods, questionnaires and interviews. Secondary data was obtained from the local Livestock Service Office, primary data sourced from respondents by purposive random sampling, as many as 15 of goat farmer in scale of 3-5 heads / farmers and 10 cocoa farmers. Each farmer has a land area of around 1000 m2 and has 100 cocoa trees, producing around 5.7 to 6.5 kg/tree/ week. Data were analyzed descriptively, quantitatively and economic feasibility analysis of B/C ratio. The purpose of this study was to analyze the economic feasibility of goat and cocoa farming businesses. The results showed that, almost all of the land belonged by farmers. The farmer business continue to run well, the worker of the goats business and cocoa is quite different. For the goats business as much as 160.56 days/year and for cocoa businesses 262.28 days/year. The profit of goat as much 5.392.060 IDR/year B/C 1.8. The capital of expenditure was 1.714.200 IDR/year. So that the profits obtained 3.677.860 IDR/year. The advantage of cocoa farmers is 67.507.200 IDR/ year B/C 2.7, The capital of expenditure of 7.2142.00 IDR/year. So that the cocoa profits obtained of 60.293.000 IDR/year. It is concluded that the goat and cacao business can be profitable for farmers. Then the business as financially economically feasible to develop further.